Study of Language Style in Hillary Clinton's speech - Susatyo, Budi; Wardhono, Agus (Jetlal, 2019)
This study aims to gain an understanding and description of the Language Style used by Hillary Clinton are: to describe the Language style used in Hillary Clinton's speech, entitled: "Hillary Clinton makes history speech" and to determine the Language style used by Hillary Clinton in her speech entitled: "Hillary Clinton makes history speech". The goal of this study is a study of the Language Style in a speech on Youtube com with its subtitle, on March 14, 2018 entitled "Learn English Hillary Clinton makes history speech". The data collection method used in this research is by listening, reading, writing and recording Hillary Clinton's speech texts repeatedly and understanding, identifying, and clarifying the style of language used during the speech. This research is qualitative descriptive research because in this research is explored to the whole speech of Hilary Clinton with the aim of analyzing and determining the type of suitable Language Style. The subject of this study is Hillary Clinton's speech entitled: "Hillary Clinton makes history speech". The use of language style in Hillary Clinton's speech can facilitate understanding. Complex ideas may be conveyed more clearly through figurative language and slogan rethorically. Stored messages can help to 'alert' a message. The use of various syntactic patterns or figurative words can help audiences remember an important element in the message. The messages conveyed can increase the persuasion appeal